Professional Development of Teachers in Bandar Aceh, Indonesia: A Case of SMA Negeri 1 Sigli - Multhaza, Multhaza; Yusrizal, Yusrizal; Bahrun, Bahrun (Jurnal Pendidikan Progresif, 2020)
Professionalism Development of Teachers in Bandar Aceh, Indonesia: A Case of SMA Negeri 1 Sigli. Objectives: This study aims to find and describe the development of teacher profesionalism in SMA Negeri 1 Sigli with regard to : (1) planning the development of teacher profesionalism, (2) implementing the development of teacher teacher professionalism and (3) constraints in developing teacher professionalism. Methods: This study uses a descriptive method with a qualitative approach. Data collection techniques are carried out through interviews, observation and documentation. The subjects in this study were school principals, teachers and school supervisors. Findings: The results of the study show that: (1) teacher development planning has been carried out well and in detail, planning is carried out by teachers, schools and educational institutions; (2) the implementation of teacher development has been carried out properly and effectively in accordance with the principles and procedures for the continuous development of teachers; (3) constraints faced in teacher development in the form of the ability to use ICT that has not been comprehensive, the time of implementation, and financing in self-development.Keywords: Teachers professional development, qualitative approach, Indonesia.DOI: 10.23960/jpp.v10.i3.202009